The impact of firm-level transparency on the ex ante risk decisions of insurers: Evidence from an empirical study - Ming Dong (Goethe University Frankfurt, International Center for Insurance Regulation (ICIR), 2014)
A greater firm-level transparency through enhanced disclosure provides more information regarding the risk situation of an insurer to its outside stakeholders such as stock investors and policyholders. The disclosure of the insurer's risktaking can result in negative influences on, for example, its stock performance and insurance demand when stock investors and policyholders are risk-averse. Insurers, which are concerned about the potential ex post adverse effects of risk-taking under greater transparency, are thus inclined to limit their risks ex ante. In other words, improved firm-level transparency can induce less risktaking incentive of insurers. This article investigates empirically the relationship between firm-level transparency and insurers' strategies on capitalization and risky investments. By exploring the disclosure levels and the risk behavior of 52 European stock insurance companies from 2005 to 2012, the results show that insurers tend to hold more equity capital under the anticipation of greater transparency, and this strategy on capital-holding is consistent for different types of insurance businesses. When considering the influence of improved transparency on the investment policy of insurers, the results are mixed for different types of insurers.
Keywords: 330; transparency; risk-taking; market discipline